PENGARUH PEMBERIAN KOMPOS TANDAN KOSONG KELAPA SAWIT (TKKS) DAN P2O5 TERHADAP PERTUMBUHAN DAN PRODUKSI PADI BERAS MERAH - Muhammad ' Iqbal; Elza ' Zuhry; Adiwirman ' ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The objective of this research was to determine the effect of TKKS compost, P2O5 and TKKS interaction with the P2O5 as well as to get the best dose for growth and production of red rice. This research was conducted in the agricultural experimental unit, Agriculture Faculty, Riau University, Bina Widya Street, sub-district of Simpang Baru, district of Tampan, Pekanbaru. This research was conducted for six months from  May until October 2015. The study arranged experimentally using Randomized Block Design (RBD) factorial. The first factor was TKKS with 4 levels consisting of: 2,5 ton/ha, 5 ton/ha, 7,5 ton/ha and 10 tons/ha and second factor was P2O5 with 4 levels consisting of: 15,525 kg/ha  (TSP33,75 kg/ ha), 31,05 kg/ha (TSP 67,5 kg/ ha), 46,575 kg/ha (TSP 101,25 kg/ha and 62,1 kg/ha (TSP 135 kg/ha). The parameters those observed were plant height, number of maximum tillers,  number of productive tillers, the panicle emergence age, panicle length, number of grains per panicle, filled grain percentage, dry milled grain weight/m2, and weight of 1000 grains milled rice.Analysis of variance and HSD 5% was used for data analysis. The results of research suggested that an increase in all variable observations with increasing dose of treatment. Dry milled grain weight/m2 positively correlated with all the variable observations except for the observation panicle age youth are correlated negatively. TKKS 7.5 ton/ ha and P2O5 46,575 kg/ha treatment can be used as combination to increase growth and yield of red rice.   Keywords: red rice, TKKS, P2O5